Diabetes: how to manage gestational diabetes mellitus - S Mimi Mukherjee; Aimee Dawson (BioExcel Publishing Ltd, 2022)
Due to worldwide increases in obesity and average maternal age, the incidence of gestational diabetes mellitus (GDM) is increasing. The primary treatment of GDM is medical nutrition therapy but approximately 15-30% of individuals need pharmacotherapy to reach blood glucose goals to minimize the adverse consequences of hyperglycaemia. In the past, regular and neutral protamine Hagedorn insulin were the mainstays of pharmacological treatment for GDM due to their well-established safety; however, because they are administered as injections and require strict timing of doses and meals to minimize hypoglycaemia, alternatives are often sought. The research around the treatment of GDM continues to evolve as insulin analogues and oral agents are studied in clinical trials. The short-term and long-term effects of treatment choices on both mothers and progeny are being evaluated, and this narrative review summarizes the current state of information available regarding the treatment of GDM.